Efektifi tas Ekstrak Daun Sirih Merah (Piper Crocatum) Terhadap Kadar Hambat Minimum Dan Kadar Bunuh Minimum Bakteri Salmonella typhi - Moch Achwandi; Azizah Khoiriyati; Soewito Soewito (IJNP (Indonesian Journal of Nursing Practices), 2015)
Research Background : Typhoid fever is a systemic infectious disease caused by Salmonella typhi. The incidence rate in Indonesia is still high at 600000-1500000 patients annually with a CFR of 10%. The high rates of morbidity and mortality, moving the parties attempt to resolve this issue. The role of the nurse in this case one of them is to provide nursing care to the provision of complementary therapies. One of the medicinal plant commonly used empirically for complementary therapies is red betel (Piper crocatum).Objective: To determine concentration of red betel leaf extract (Piper crocatum) eff ectiveness against Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) bacteria Salmonella typhi.Method: Type of laboratory experimental studies in vitro with posttest only control group design. Red betel leaf extract has been created by default then tested on Salmonella typhi bacteria. The test method has been conducted with serial dilutions of liquid dilution. Repetition 4 times. Statistical test used was the Kruskal-Wallis test.Results : The results showed that the extract of red betel leaf has a MIC which can not be determined because of the turbidity of the suspension and MBC extract at a concentration of 12.5 %.Conclusion : Eff ectiveness of red betel leaf extract against Salmonella typhi bacteria MIC can not be determined. Red betel leaf extract is eff ective against the bacteria Salmonella typhi MBC. Dose of red betel leaf extract is eff ective against the bacteria Salmonella typhi MBC is at a concentration of 12.5%.Keywords: Red betel (Piper crocatum) – Minimum Inhibitory Concentration - Minimum Bactericidal Concentration - Salmonella typhi